2009
DOI: 10.1177/039463200902200204
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lymphocytic Leukemia-Associated Pure Red Cell Aplasia

Abstract: Pure red cell aplasia (PRCA) is a well-known marrow failure which may be acquired or constitutional/congenital, as the Diamond-Blackfan syndrome. Acquired PRCA may show as a primary hematological disorder or secondary to an associated disease, infection or drug. PRCA rarely complicates chronic lymphocytic leukemia (CLL), may occur anytime in the course of the disease and, in this context, it is a minority of total PRCA. Anemia due to PRCA in CLL patients must be carefully evaluated and differentiated from othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Alemtuzumab has been reported to be active in steroid-refractory cases. 85 In the very refractory cases, allogeneic stem cell transplantation maybe necessary.…”
Section: Autoimmune Cytopeniasmentioning
confidence: 99%
“…Alemtuzumab has been reported to be active in steroid-refractory cases. 85 In the very refractory cases, allogeneic stem cell transplantation maybe necessary.…”
Section: Autoimmune Cytopeniasmentioning
confidence: 99%
“…MBL, an increasingly recognized entity with an approximate incidence of 5% in individuals older than 60 years with normal lymphocyte counts, has a 1.1% yearly progression rate to CLL and does not usually warrant extensive evaluation . However, as illustrated here, autoimmune hematologic phenomena can precede the development of CLL and are recognized to be more frequent when the malignant clone's heavy‐chain variable region sequence is unmutated . To our knowledge, this is the first report of MBL presenting with AVWS.…”
Section: Discussionmentioning
confidence: 82%
“…However, an alternative notion supporting the main role of T and NK-cells in suppression of erythropoiesis has also been proposed (reviewed by D'Arena and Cascavilla [6]). In fact, experimental studies showed that the inhibition of erythropoiesis is due to the dysfunction of the so-called γδ T cells carrying the Fc receptor for IgG (CD16) [57–64].…”
Section: Pathogenesismentioning
confidence: 99%
“…The combination of FAMP, cyclophosphamide and anti-CD20 monoclonal antibody rituximab (FCR regimen) has emerged as the current standard of care in the treatment of younger CLL patients [66]. AIHA may complicate FAMP therapy [6]. Table 4 summarizes data on the incidence of AIHA in FAMP-treated CLL patients from some of the largest studies published so far.…”
Section: Fludarabine-related Autoimmune Aihamentioning
confidence: 99%
See 1 more Smart Citation